Neuroprotective effects of TUDCA in Parkinson’s disease: dissecting the anti-oxidant and anti-inflammatory effects of this bile acid in the mouse cerebral cortex - Mendes, Mariana de Oliveira (2018)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017